Gharar Harga pada Industri Mikro dan Kecil Makanan Di Jakarta Timur, Bekasi, dan Gresik - Wily Mohammad; Nabilla Ryca Maulidiyah (CV. Syntax Corporation Indonesia, 2021)
Gharar is one of the things that is prohibited in buying and selling in Islam. The purpose of this research is to determine the practice of price gharar in micro and small industries in the food and beverage sector in East Jakarta City, Bekasi City, and Gresik Regency seen from the menu and food prices. The benefit of this research is to ensure certainty, harmony, safety, and avoid fraud and hostility towards sellers and buyers. In addition, as a suggestion for the government of East Jakarta City, Bekasi City, and Gresik Regency so that there is no practice of price gharar in buying and selling, especially for micro and small industries in the food and beverage sector. This type of research is descriptive quantitative. The population in this study is the number of micro and small industries in the three cities. Determination of the sample in this study using the Taro Yamane sampling technique, with a significance level of 95%. From the results of these calculations, 395 industries were selected as research samples. The results of this study were from 395 samples of micro and small industries in the food and beverage sector in East Jakarta City, Bekasi City, and Gresik Regency, 298 samples (75.44%) did not have menus and prices. Based on the results of interviews with several samples, there is a lack of understanding, information, and trust in buying and selling in Islam, even understanding about buying and selling in general is still lacking. It is recommended to academics, government, and business activists to provide socialization for information and teaching for this industry about the importance of making and serving menus with food and beverage prices.